Higiene dan Sanitasi pada Pengolahan Makanan di Pondok Pesantren Moderen Darussalam Gontor Putri 4 di Desa Lamomea Kecamatan Konda Kabupaten Konawe Selatan - Pratiwi, Evie Fitrah; Meilan, Meilan (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2017)
Personal hygiene is a clean attitude and behavior of food organizers so that food is not contaminated. Some things that must be considered include health checks, hand washing, nose, mouth, teeth and ear hygiene, clothing hygiene and good living habits. and disease in humans. Hygiene and sanitation are important in determining the quality of food. This study uses a descriptive study design with a qualitative approach. The instruments used in this study were interview guidelines and observation checklist sheets. The results of the study in general the application of hygiene and sanitation in food processing has been carried out in accordance with applicable theories and standards. However, there are still discrepancies in the application of hygiene and sanitation in food processing. The conclusion in this study is that food processing is in accordance with the principles of food administration and applies the principles of hygiene and sanitation in food handling. However, the lack of adequate facilities causes environmental sanitation in food processing to be unsuitable